2020
DOI: 10.1177/2150132720961265
|View full text |Cite
|
Sign up to set email alerts
|

On the Association Between Social Determinants of Health and Disability in Stroke-Free Older Adults Living in Rural Settings. The Three Villages Study

Abstract: Background High social risk, as quantified by the social determinants of health (SDH), may lead to disability. This association has not been well explored in remote settings. Using the three Villages Study cohort, we assessed the association between SDH and disability among stroke-free older adults living in a rural Ecuadorian community. Methods SDH were measured by the use of the Gijon Scale and disability by the Functional Activities Questionnaire. All participants had a brain MRI to assess subclinical bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Findings of the present work, as well as those of other studies conducted in similar rural communities, underline the importance of selecting the proper field instrument to investigate SDH in underserved populations. 3,24 SDH assessment is not a matter of “one-size-fits-all”, and must be tailored according to the specific characteristics of the study population. SDH vary according to the level of development of a given community and their assessment must be adapted consequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of the present work, as well as those of other studies conducted in similar rural communities, underline the importance of selecting the proper field instrument to investigate SDH in underserved populations. 3,24 SDH assessment is not a matter of “one-size-fits-all”, and must be tailored according to the specific characteristics of the study population. SDH vary according to the level of development of a given community and their assessment must be adapted consequently.…”
Section: Discussionmentioning
confidence: 99%
“…1 SDH have a substantial impact on health status (particularly in vulnerable populations) and may result in the occurrence or progression of chronic conditions and diseases. 2,3 Moreover, SDH have been associated to increased stroke incidence and worse outcomes after a stroke. [4][5][6][7][8] However, specific cerebrovascular consequences of SDH have not been well evaluated to date.…”
mentioning
confidence: 99%
“…Unfortunately, heterogeneity of designs across studies preclude valid conclusions on its prevalence, but the burden of cognitive decline in these settings is probably on the rise 16–19 . Likewise there is no information on the role of SDH in cognitive performance, although a previous study from our group found a significant association between high social risk (as measured by SDH) and disability in rural Ecuadorian settings 7 . Taking advantage of an already established observational cohort of community‐dwellers living in rural villages located in coastal Ecuador, 20 the present study examines the association between SDH and cognitive performance in older adults residing in these villages.…”
Section: Introductionmentioning
confidence: 92%
“…These determinants have a significant impact on the development of functional independence and on the health status of individuals, including the occurrence and progression of several chronic conditions and diseases 2–5 . SDH are of particular importance in fragile populations, such as older adults, who are prone to develop depression, increased cognitive complaints or disability in the setting of high social risk 6,7 . Indeed, several studies have suggested a link between SDH and poor cognitive performance, including dementia 8–10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation